The CARM1 epigenetic enzyme inhibits cross-presenting dendritic cell function in cancer immunity - Xixi Zhang; Sherin Xirenayi; Ye Zhao; Wen Wang; Yuyang Han; Miguel Sobral; Shawn Kang; Chi Zhang; Graham L. Barlow; Jason Pyrdol; Jae-Won Cho; Kun Huang; et al. (Science, 2026)
The cancer-immunity cycle requires cross-presenting type I conventional dendritic cells (cDC1s) that induce T cell–mediated immunity, but therapeutic strategies for enhancing intratumoral cDC1 function are currently inadequate. We found the epigenetic enzyme CARM1 (coactivator-associated arginine methyltransferase 1) to be a selective negative regulator of cancer antigen presentation by cDC1s but not cDC2s. Inactivation of the Carm1 gene promoted cDC1 antigen cross-presentation, activation, and accumulation in tumors, and a CARM1 inhibitor enhanced cDC1-mediated priming of T cells by means of a cancer neoantigen vaccine. CARM1 inhibition increased chromatin accessibility at BATF3-Jun and RelA sites that are critical for cDC1 function and activation. Transforming growth factor–β regulated Carm1 expression, which suggests that CARM1 inactivation enhanced intratumoral cDC1 function without altering cDC1 homeostasis. These studies identify CARM1 as a potential therapeutic target for enhancing the antitumor function of mouse and human cDC1s.